Oral History Program Interview : Alvin Bryan Laird and Rosie Lee Harlas Laird - Laird, Rosie Lee Harlas; Laird, Alvin Bryan
Alvin Laird (born in Frederick, Oklahoma in 1908) and Rosie Laird (born in Cloud Chief, Oklahoma in 1912) stopped in Earlimart, California in 1935 before moving on to the Imperial Valley. The Lairds' interview sheds light on how minorities and migrants were taken advantage of at work, life in ditch, government, apartment, and private camps, the effects of New Deal policies, the parallels between The Grapes of Wrath and real "Okies," the California border patrols, prejudices towards "Okies" and African Americans, organizing and strikes in the fields, life in the CCC, perceptions towards welfare use, what "Okie" means, and a woman's perspective.